The New Encyclopedia of Science : Ecology and Environment : The Cycles of Life - Morgan, Sally and Allaby, Michael; Advisory Editors Moore, Peter Dr. and Targer, James C. Dr. (New York Oxford University Press, 2003)
A color-illustrated encyclopedia of ecology and the environment containing short definitions to approximately four hundred terms, cross-referenced to more than forty thematic spreads. Also includes knowledge maps and a time line
Include Color Illustration and Index
Keywords: Ecology -- Environmental sciences